“No sir, she was not a fool in the field”: Gendered risks and sexual violence in immersed cross-cultural fieldwork - Ross, Karen (The Professional Geographer, 2015)
It is rare to hear about the gendered risks of field work. My experiences with sexual violence with key informants forced me to assume a variety of defensive behaviors, which ran counter to the ways that scholarly discussions of methods tend to emphasize the importance of reducing distance and shifting power away from the researcher in a cross-cultural context. By considering gendered risks, I question the extent to which an idealized male researcher is still viewed as the archetype from which methods are conceptualized and practiced, and the implications are then discussed
Keywords: discipline; ethnographie; genre; pouvoir; ressource en ligne; sciences humaines; thématiques; violences; violences sexistes et sexuelles